Bone marrow pathology - Bain, Barbara J.; Ohio Library and Information Network (Chichester, England : John Wiley & Sons Ltd, 2025)
The diagnosis and treatment of bone marrow pathologies is one of the most critical areas of medical research and care. For years, Bone Marrow Pathology has served as the essential reference and teaching tool in the field of haematology, with an authoritative treatment of the subject written by acknowledged leaders in the field. Now fully updated to reflect urgent new changes to the theory and practice of haematology, it promises to serve a new generation of practitioners. In the book, the characteristics and function of normal bone marrow are extensively discussed. Bone marrow pathology, including both aspirate films and trephine biopsy sections, is examined in a clinical context. The content is augmented by discussion of the peripheral blood findings and supplementary bone marrow tests
Includes bibliographical references and index
Keywords: Bone marrow; Bone Marrow